Survival Rate of Lung Adenocarcinoma Patients Receiving EGFR - Tyrosine Kinase Inhibitor Targeted Therapy - Ungky Agus Setyawan; Rezki Tantular; Chaerani Bahar (Fakultas Kedokteran Universitas Brawijaya, 2023)
Globally, lung cancer is by far the leading cause of death by cancer-which contribute to 2.094 million death-with the highest toll from cancer being 1.8 million. Currently, lung cancer therapy has developed from chemotherapy to targeted therapy, such as Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor (EGFR-TKI). This study aimed to assess the survival rate of adenocarcinoma cell lung cancer patients who received EGFR-TKI therapy at the Pulmonary Clinic of Dr. Saiful Anwar General Hospital Malang. This study was a retrospective study using patient medical records between 2017 and 2020. The data were processed and analyzed using the Chi-Square test. The number of samples was 117 patients consisting of 63 patients receiving Gefitinib therapy, 36 patients receiving Afatinib therapy, and 18 patients receiving Erlotinib therapy. There were no significant differences between variables of age, sex, smoking history, stage, and exon mutations with 1-year survival. Gefitinib therapy has a higher average survival time than Afatinib and Erlotinib. However, the 1-year survival rate (YSR) was highest on Afatinib. The Middle Survival (MS) of the three regimens is almost the same, about 300 days. Statistical data showed no relationship between survival and the treatment regimen given (p=0.187). The most common side effect of TKI is skin rash. This research should be carried out with a larger sample to minimize bias.